COVID-19 transmissibility: lockdown a forced agenda or need of hour? - Chauhan, Nidhi; Rattan, Saurabh; Sharma, Gopal Ashish; ., Priyanka; Singh, Resham; Sharma, Priya (International Journal Of Community Medicine And Public Health, 2021)
Background: A corona virus identified in 2019, SARS-CoV-2, has caused a pandemic of respiratory illness, called COVID-19. COVID-19 has been cited responsible for over more than four million deaths across the world. Consequentially, COVID-19 had resulted in various residual health problems in infected individuals during the illness period and in some even after the recovery. Methods:A cross-sectional survey having 10-item questionnaire was developed using Google forms. The questionnaire was made available to the participants through all available social networking platforms such as email, WhatsApp etc. according to the suitability of the participant. Data were collected and entered in a Microsoft Excel spreadsheet, cleaned for errors and analysed using Epi-info version 7.2.1.0 software. Results: The study found that majority of people agreed to the implementation of lockdown and only 6.1% said that lockdown should not be implemented. Among those who agreed to the implementation of lockdown, 50.2% had opined that the lockdown should be implemented only based on the number of cases in the individual state. Conclusions:India, still as a developing nation has giant leaps to take to clear through this pandemic crisis. This study concludes that the general population was clear about the essentiality of the lockdown however a segment of the population had the implications in a way that was affecting their livelihood hence acutely changing their perception otherwise.